2015
DOI: 10.1063/1.4923258
|View full text |Cite
|
Sign up to set email alerts
|

Group III-nitride nanowire structures for photocatalytic hydrogen evolution under visible light irradiation

Abstract: The performance of photochemical water splitting over the emerging nanostructured photocatalysts is often constrained by their surface electronic properties, which can lead to imbalance in redox reactions, reduced efficiency, and poor stability. We have investigated the impact of surface charge properties on the photocatalytic activity of InGaN nanowires. By optimizing the surface charge properties through controlled p-type dopant (Mg) incorporation, we have demonstrated an apparent quantum efficiency of ∼17.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 44 publications
2
26
0
Order By: Relevance
“…[103,104] GaN-based alloys and nanostructures exhibit near-ideal thermodynamic and kinetic attributes and advantages [105] over other known photocatalysts, including extreme chemical stability, high absorption coefficients and tunable bandgap to encompass nearly entire solar spectrum (shown in Figure 10) while straddling water redox potential for up to %50% indium incorporation. [10,106] Moreover, the nonpolar surfaces of GaN are highly reactive for spontaneous dissociation of water molecules, [107,108] and possess low energy barrier for proton diffusion. [109,110] GaN-based nanocrystals provide additional advantages, including significantly reduced defects and dislocations when grown on foreign substrates, efficient light absorption and charge carrier separation, and enhanced stability due to the N-rich surfaces that can protect against photo-corrosion and oxidation.…”
Section: Artificial Photosynthesismentioning
confidence: 99%
“…[103,104] GaN-based alloys and nanostructures exhibit near-ideal thermodynamic and kinetic attributes and advantages [105] over other known photocatalysts, including extreme chemical stability, high absorption coefficients and tunable bandgap to encompass nearly entire solar spectrum (shown in Figure 10) while straddling water redox potential for up to %50% indium incorporation. [10,106] Moreover, the nonpolar surfaces of GaN are highly reactive for spontaneous dissociation of water molecules, [107,108] and possess low energy barrier for proton diffusion. [109,110] GaN-based nanocrystals provide additional advantages, including significantly reduced defects and dislocations when grown on foreign substrates, efficient light absorption and charge carrier separation, and enhanced stability due to the N-rich surfaces that can protect against photo-corrosion and oxidation.…”
Section: Artificial Photosynthesismentioning
confidence: 99%
“…The growth conditions were optimized after several iterations for better crystalline quality and photocatalytic performance in overall water splitting reaction. Instead of multi-stack InGaN:Mg/GaN:Mg layers 35 , 36 , a continuous InGaN:Mg layer was grown spontaneously on top of GaN:Ge nanowire template followed by a final GaN:Mg capping layer (relatively smaller than InGaN in length, in proportion to fraction of UV region in the spectrum). A nitrogen flow rate of 1.0 standard cubic centimeters per minute (sccm), and a forward plasma power of ~350 W were used during the growth.…”
Section: Methodsmentioning
confidence: 99%
“…To improve the carrier extraction process, researchers have observed that controlling the band bending process in nanostructured In x Ga 1 − x N photo-electrode design and optimizing it is of utmost importance. Such a design has shown a considerable absorption improvement in the PEC process as compared to undoped samples, especially in UV and violet spectrum region [75]. In another study, Alvi et al achieved In incorporation beyond 40% in the design of nanostructured In x Ga 1 − x N using PAMBE method and achieved notable enhancement in photocatalytic activity [76].…”
Section: Light Management For Photoelectrochemical Cells Using Periodmentioning
confidence: 99%